Wszechświat rozszerza się. Teorii toposów horyzonty dawne i nowe - Wyglądacz, Krzysztof (Res Facta Nova, 2025)
This paper shall serve as an overview of recent publications on the field of topic theory in music. Its point of departure is marked by three definitions of musical topic, formulated by Danuta Mirka, Eero Tarasti and Joan Grimalt, respectively. According to these definitions, musical topics are recurrent features of musical style, which, taken out of their primary context and used in another one, form associations – often, but not always referential – to some established social and cultural conventions. The main body of the text is laid out in five main sections. In the first section the concept of musical topics is traced back to its origins in Leonard Ratner’s Classic Music. Expression, Form and Style (1980). The second follows its development in subsequent decades in general and broadening its scope in particular. Three large-scale publications – Joan Grimalt’s Mapping Musical Signification (2021), The Routledge Handbook of Music Signification edited by Esti Sheinberg and William P. Dougherty (2020) and Musical Topics and Musical Performance edited by Julian Hellaby (2023) – are examined in the third section. In the fourth, relations between topics and 18th-century schemata (as defined by Robert Gjerdingen) and 19th- and 20th-century leitmotivs are examined. The last section outlines some of the boundaries of topic theory, especially its ambiguous status as historically correct mode of analysis and its difficulty in providing relevant insight into musical syntax.